Prevalence of Molecular Subtypes of Breast Carcinoma and Its Comparison between Two Different Age Groups: A Retrospective Study from a Tertiary Care Center of Northeast India - Sharma, Jagannath Dev; Khanna, Sachin; Ramchandani, Shubhra; Kakoti, Lopa Mudra; Baruah, Argha; Mamidala, Vinay (South Asian Journal of Cancer, 2021)
Objective The aim of the study is to see the prevalence of different molecular subtypes in breast cancer patients among two different age groups: ≤40 years and >40 years.Materials and Methods Retrospective study was conducted from January 2019 to December 2019. We studied 568 cases of breast carcinoma and classified them into four molecular subtypes—luminal A, luminal B, human epidermal growth factor-2 (HER 2), and triple negative. Cases were divided into two different groups: (1) ≤40 years and (2) >40 years.Statistical Analysis was done by using SPSS software version 20.0.Results Out of 568 cases, 151 (26.6%) were ≤40 years of age and 417 (73.4%) were >40 years of age. The most common histological subtype of breast cancer was ductal carcinoma in 548 cases and the most common grade was grade III. Immunohistochemistry was done in 432 patients. In younger age group, the most common molecular subtype was luminal B (31%) followed by triple negative (20%), luminal A (14%), and then HER 2 (5.3%), while in the older age group most common molecular subtype was luminal B (27.8%) followed by triple negative (14%), HER 2 (12.2%), and then luminal A (12%).Conclusion Luminal B is found to be the most common subtype in Northeast Indian women with breast cancer, as compared with other studies in which luminal A was the most common subtype. This could be due to the reason that Ki-67 was not done in most of the other studies.
Keywords: estrogen receptor; progesterone receptor; human epidermal growth factor; luminal A; luminal B; triple negative